How can effective economic management be achieved in small states? (2004)
Opines that governments should plan for the future, and only spend what they can afford. Suggests that they should not rely on a single industry, and in planning for the future, should ensure that the country has alternative sources of income for when an important industry is adversely affected.
Keywords: ECONOMIC ADMINISTRATION